The Association Analysis of GPNMB rs156429 With Clinical Manifestations in Chinese Population With Parkinson's Disease - Liu, Jin; Li, Gen; He, Yixi; He, Guiying; Zhang, Pingchen; Shen, Xin; Zhang, Weishan; Chen, Shengdi; Cui, Shishuang; Tan, Yuyan (Frontiers in Genetics, 2020)
Background: The mechanisms of Parkinson’s disease (PD) include complicated genetic factors. The roles of newly found risk genes need to be further verified among different ethnicities. In a two-stage meta-analysis, single nucleotide polymorphism (SNP) of rs156429 in glycoprotein nonmetastatic melanoma protein B (GPNMB) was reported to be associated with PD. So far clinical studies have focused on association between rs156429 and PD onset, however there is little evidence linking rs156429 with PD symptoms. Objective: This study aimed to investigate the possible association of GPNMB rs156429 with PD manifestations among southeastern Chinese people. Methods: Demographic variables, disease-related factors, and motor and non-motor assessments of 511 PD patients were collected. Polymerase chain reaction (PCR) and SNaPshot technique were used to detect GPNMB rs156429. The associations of rs156429 with PD rating scales and clinical manifestations were analyzed by Kruskal-Wallis test and logistic regression model separately. Results: Kruskal-Wallis test and logistic regression model failed to reveal an association between GPNMB rs156429 and scores from Montreal Cognitive Assessment (MoCA) (p = 0.037; p = 1.000 after correction), and pain symptoms of 511 PD patients (p = 0.008, OR = 0.59, 95% CI = 0.40-0.87, overdominant model after adjustment; p = 0.168 after correction, overdominant model after adjustment). However, further analysis based on genders showed that GPNMB rs156429 might have a trend for being associated with cognitive dysfunction (Mini-Mental State Examination (MMSE), p = 0.064 after correction; MoCA, p = 0.064 after correction) and pain symptoms (p = 0.063 after correction, overdominant model after adjustment) in female PD patients but not male patients. Conclusions: This study revealed that GPNMB rs156429 might have a trend for being associated with cognitive dysfunction and pain symptoms of female PD patients in the southeastern Chinese population. Further studies from a larger sample size are needed to confirm these findings.